Serious drug reactions to carbamazepine in oncologic patients after x-ray treatment - Kansky, Aleksej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
Carbamazepine is a valuable and widely used drug for treatment and prevention of epileptiform fits and further neurological conditions. Milder general symptoms like dizziness or drowsiness or cutaneous side effects like rashes, pruritus, urticaria, or multiform erythema are not unusual. Sometimes serious cutaneous adverse reactions e.g., Stevens Johnson syndrome, generalized erythroderma or even toxic necrolysis may appear. We report on four cases: in three female patients, who have been operated for malignant brain tumors and were given carbamazepine for prevention of seizures, partial erythroderma developed; the fourth died from toxic epidermal necrolysis. All were treated with x-rays, in the female patients cutaneous manifestations disappeared aftersystemic treatment with corticosteroids and replacement of carbamazepine with other anticonvulsive drugs.
Keywords: Adult; Adverse Effects; Brain Neoplasms; Carbamazepine; dermatitis; Dermatitis eksfoliativni; Dermatitis, Exfoliative; dermatologija; Eksantem; Exanthema; Karbamazepin; kožne spremembe; Middle Age; Možganske novotvorbe; Odrasli; Radiotherapy; Srednja leta; zdravila